Endocrinal dysfunction in children with Down syndrome - Kotb Abbass Metwalley; Hekma Saad Farghaly (Korean Society of Pediatric Endocrinology, 2022)
Down syndrome (DS) is the most common genetic disorder in live-born infants. Children with DS are at increased risk of numerous endocrinal comorbidities. The information contained in this article will provide pediatricians with a narrative overview of different presentations, diagnoses, and management recommendations of various endocrinal disorders in children with DS. We systematically searched PubMed, Embase, Google Scholar, MEDLINE, EBSCO, and Science Direct, and potentially relevant articles were identified and retrieved from electronic and print journals.